IMPLEMENTASI TEORI BELAJAR KOGNITIF DAN BEHAVIORISTIK DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Sujana Adnyana, I Made (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of cognitive and behaviorist learning theories in science education at the elementary school level and their impact on student learning outcomes. The cognitive approach emphasizes mental processes in understanding information, while the behaviorist approach focuses on observable behavioral changes resulting from stimulus-response interactions. This qualitative study employed observation and interviews with teachers and students across several elementary schools. Findings indicate that the application of cognitive strategies, such as concept mapping and the use of visual media, assists students in organizing information and establishing connections between concepts, thereby deepening their understanding of the material. Additionally, the application of behaviorist principles through positive reinforcement, such as praise and rewards, effectively enhances student motivation and participation in learning activities. The combination of these two approaches has been shown to create a learning environment that is adaptive and responsive to individual student needs, ultimately improving their learning outcomes. However, the study also identifies challenges in balancing guidance and student autonomy, which require proficient pedagogical skills from teachers. Therefore, professional training and development for teachers are highly recommended to optimize the implementation of these theories in science education at the elementary school level